Legal Analysis on Defamation from the Perspective of Islamic Law and Article 12 of the Universal Declaration of Human Rights - Sidiq, Gifar; Arifin, Tajul; Fauziah, Ine (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
This research is based on the fact that defamation is an important issue that affects the honor of individuals in various legal systems. This issue has far-reaching implications, both personally and socially, requiring a comprehensive approach to protecting individual rights. This research aims to analyze defamation from two legal perspectives, namely Islamic Law and Article 12 of the Universal Declaration of Human Rights (UDHR). This study uses a normative juridical approach with a descriptive analysis method. Data were collected through a literature review of relevant primary and secondary sources. Furthermore, the data was analyzed using qualitative data analysis techniques to explore the essence of legal protection in both perspectives. The results of the study show that both Islamic Law and Article 12 of the UDHR emphasize the importance of protecting the honor of individuals. However, Islamic law highlights more social and spiritual dimensions, such as the concept of maintaining honor as part of religious obligations. Meanwhile, the UDHR focuses on the protection of individual legal rights in the context of human rights. These findings indicate the need to integrate both approaches in the Indonesian legal system to provide more comprehensive and balanced protection against defamation cases. The implication of this research is to encourage legal policies that not only protect the rights of individuals but also pay attention to the typical moral and social aspects of Indonesian society.